All diuretics used in the treatment of hypertension are not the same - Serkan Asil; Enver Atalar (KARE Publishing, 2017)
Summary- Diuretics have been used for years to treat hypertension as both a monotherapy and in combination. Hydrochlorothiazide, indapamide, and chlorthalidone have frequently been considered in the same category as thiazide diuretics, but there is no evidence that their activities are similar. Studies have shown that chlorthalidone and indapamide reduce cardiovascular morbidity and mortality; however, there is no study indicating that hydrochlorothiazide has beneficial effects on cardiovascular outcomes such as myocardial infarction, renal failure, stroke, or death. Hydrochlorothiazide has less effect on blood pressure, a high risk of metabolic side effects, and may not have pleiotropic effects. As a result, it is not accurate to evaluate chlorthalidone and indapamide as similar to thiazide diuretics. Indapamide or chlorthalidone is a better choice of diuretic for use in the treatment of hypertension.